Improved analytical energy balance model for evaluating agglomeration from a binary collision of identical wet particles. (21st September 2020) - Shabanian, Jaber; Duchesne, Marc A.; Runstedtler, Allan; Syamlal, Madhava; Hughes, Robin W.
Highlights: Model for evaluating the agglomeration of identical wet particles. Improved an analytical energy balance model by correcting viscous energy loss equations and introducing a new evaluation algorithm. Accounts for collisions of particles with different initial speeds. Rational outcomes under capillary and viscous limiting conditions with highly wetting systems. Sensitivity analysis of particle agglomeration under capillary and viscous limiting conditions. Abstract: Particle agglomeration is a common phenomenon in a large number of industries. The presence of a liquid bridge between colliding wet particles is the principal source of agglomeration in such processes as wet granulation and thermal conversion of fuels in a high temperature gas–solid fluidized bed reactor. A comprehensive agglomeration model for wet particles must incorporate both liquid capillary and viscous contributions, as well as the liquid bridge volume effect. Darabi et al. (Chem. Eng. Sci. 64 (2009) 1868–1876) developed a coalescence model for a binary collision of identical wet particles. The model provides reasonable results for wet particles with a low viscosity liquid layer, i.e., under capillary limiting conditions. However, application of this model for collisions of particles coated with a high viscosity liquid layer, i.e., under viscous limiting conditions, results in unreliable outcomes. The current study presents an improved version of Darabi et al.'s model, which (i) corrects viscous energy loss equations in the original model, thus providing reasonable outcomes under both capillary and viscous limiting conditions with highly wetting systems, (ii) accounts for the contribution of capillary force in the approach stage when estimating the initial particle speed for the separation stage, (iii) accounts for the collision of particles having different initial speeds with respect to the laboratory reference frame, (iv) employs a more reliable correlation to estimate the liquid bridge rupture distance, and (v) evaluates the collision outcome in three steps based on the values of kinetic energy parameters. We compared experimental particle-plate collision data with the predictions from agglomeration models and it showed that considering the liquid bridge volume effect and the liquid bridge rupture distance can be essential for the accurate prediction of collision outcomes. The results of sensitivity analyses with the improved agglomeration model revealed that the agglomeration outcome under capillary limiting conditions is most sensitive to the thickness of the coating layer, particle inertia, liquid surface tension, and dry restitution coefficient. Under viscous limiting conditions, proper measurement or estimation of the thickness of the coating layer, liquid viscosity, asperity height, and particle inertia are critical for evaluating the particle collision outcome.